How does digital technology enhance sustainable operations in agribusiness? A case analysis of a Chinese agricultural enterprise - Wang, Zichen; Pan, Zhongfeng; Lai, Wenling; Lu, Shan; Liu, Haitao; Wang, Xueqing; Wu, Haibo (Frontiers in Sustainable Food Systems, 2025)
BackgroundSustainable agricultural enterprise operations are pivotal for resolving market inefficiencies in global food systems including information asymmetry resource misallocation and productivity stagnation. These inefficiencies impede food security and rural development particularly amid the digital transformation of agricultural value chains.MethodGrounded in resource-based view (RBV) model and dynamic capabilities theory this study employs a single-case longitudinal design with China Joyvio Group (JVG) as the focal enterprise. The case spans three distinct transformation phases enabling rigorous causal analysis of digital technology’s impact on sustainable operations. By collating the company’s annual reports, financial reports and in-depth interviews, we finally obtained the enterprise operation records of JVG. These records contain basic data, cases and achievements, providing supporting materials for us to conduct a detailed analysis of how digital transformation can enhance performance.ResultsJVG’s dual-track digital strategy “organizational management” and “business operation” systematically resolves core inefficiencies through four empirically validated mechanisms: (1) Organizational empowerment via knowledge assetization; (2) Operational resilience through end-to-end digital integration; (3) Industrial chain innovation via three smart platforms “Agricultural and Food Digital Intelligence Brain,” “YunAgri Prime,” “YunAgri Select,” enabling full-chain standardization and resource optimization; (4) Value chain upgrading with 28.6% higher product premiumization; (5) and he ecological and environmental benefits have been greatly enhanced. These mechanisms collectively address the efficiency, information, and resource predicaments of traditional agriculture.ConclusionIt provides a quantitatively validated framework for agricultural enterprises to achieve sustainable operations balancing economic viability social equity and environmental sustainability. Findings offer actionable policy insights for national agricultural digitalization strategies and address a critical empirical gap in agricultural economics literature.